Effects of exposure to loud noise on the hearing of the residents of Calabar, Nigeria - Asuquo, Ubon; Onuu, Michael; Asuquo, Affiong (Canadian Acoustics, 2012)
The article examines the effects of exposure to loud noise on the hearing of the residents of Calabar, Nigeria. To determine how related the subjective responses, assessed by the use of questionnaires as the study instrument were to the objective responses measured with the sound level meter, the coefficients of correlation were calculated for the noise measurements. Noise is a disturbance to the human environment that is escalating at such a high rate that it will become a major threat to the quality of human lives if nothing is done to reduce it. Noise has been a constant threat since the industrial revolution. Too much noise exposure may cause a temporarily change in hearing or a temporarily ringing in your ears (tinnitus). These short-term problems usually go away within a few minutes or hours after leaving the noise. However, repeated exposures to loud noise can lead to permanent, incurable hearing loss or tinnitus.